Development of Mathematical Thinking of Mathayomsuksa 1 Students by Using Instruction Activities Based on Cognitive Guided Instruction and Questioning Techniques of Badham / การพัฒนาการคิดเชิงคณิตศาสตร์ของนักเรียนชั้นมัธยมศึกษาปีที่ 1 โดยใช้กิจกรรมการเรียนรู้แบบการสอนแนะให้รู้คิด (CGI) ร่วมกับเทคนิคการใช้คำถามของบาดแฮม (Badham) - ชุติมา ฉุนอิ่ม และวนินทร สุภาพ, Chootima Chunim and Wanintorn Supap / (Journal of Community Development Research (Humanities and Social Sciences), 2015)
งานวิจัยนี้มีวัตถุประสงค์เพื่อ 1) เปรียบเทียบการคิดเชิงคณิตศาสตร์ของนักเรียนชั้นมัธยมศึกษาปีที่ 1 ก่อนเรียนและหลังเรียน โดยใช้กิจกรรมการเรียนรู้แบบการสอนแนะให้รู้คิด (CGI) ร่วมกับเทคนิคการใช้คำถามของบาดแฮม (Badham) 2) เปรียบเทียบการคิด เชิงคณิตศาสตร์ของนักเรียนชั้นมัธยมศึกษาปีที่ 1 หลังการจัดกิจกรรมการเรียนรู้แบบการสอนแนะให้รู้คิด (CGI) ร่วมกับเทคนิคการใช้คำถามของบาดแฮม (Badham) กับเกณฑ์ร้อยละ 70 กลุ่มตัวอย่างเป็นนักเรียนชั้นมัธยมศึกษาปีที่ 1 ภาคเรียนที่ 2 ปีการศึกษา 2557 จำนวน 27 คน โดยเครื่องมือที่ใช้ในการวิจัย ได้แก่ แผนการจัดกิจกรรมการเรียนรู้แบบการสอนแนะให้รู้คิด (CGI) ร่วมกับเทคนิคการใช้คำถามของบาดแฮม (Badham) แบบวัดการคิดเชิงคณิตศาสตร์ แบบสัมภาษณ์การคิดเชิงคณิตศาสตร์ และแบบสังเกตพฤติกรรมการคิดเชิงคณิตศาสตร์ สถิติที่ใช้ทดสอบ ได้แก่ ค่ามัชฌิมเลขคณิต ค่าส่วนเบี่ยงเบนมาตรฐาน สถิติทดสอบค่าที (t-test) และการวิเคราะห์สรุปอุปนัย (Analytic Induction) ผลการวิจัย พบว่า 1) นักเรียนที่เรียนโดยใช้กิจกรรมการเรียนรู้แบบการสอนแนะให้รู้คิด (CGI) ร่วมกับเทคนิคการใช้คำถามของบาดแฮม (Badham) มีการคิดเชิงคณิตศาสตร์หลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 และเมื่อเปรียบเทียบการคิดเชิงคณิตศาสตร์รายด้าน ได้แก่ ด้านการแก้ปัญหา ด้านการให้เหตุผล และด้านการนำเสนอตัวแทนความคิดของนักเรียน พบว่า หลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 2) นักเรียนที่เรียนโดยใช้กิจกรรมการเรียนรู้แบบการสอนแนะให้รู้คิด (CGI) ร่วมกับเทคนิคการใช้คำถามของบาดแฮม (Badham) มีการคิดเชิงคณิตศาสตร์หลังเรียนสูงกว่าเกณฑ์ร้อยละ 70 อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 กล่าวโดยสรุป การจัดกิจกรรมการเรียนรู้แบบการสอนแนะให้รู้คิด (CGI) ร่วมกับเทคนิคการใช้คำถามของบาดแฮม (Badham) นั้น มุ่งเน้นให้นักเรียนแก้ปัญหาโดยวิธีการที่หลากหลายและแตกต่างกันตามศักยภาพของตน รวมทั้งมีโอกาสได้พูดคุยและนำเสนอ ร่วมกับการตั้งคำถาม ที่ช่วยกระตุ้นความคิดของนักเรียน ช่วยให้นักเรียนได้พัฒนาการคิดและอ้างอิงเหตุผลในการตอบคำถาม นำไปสู่การพัฒนาการคิดเชิงคณิตศาสตร์ของนักเรียนในด้านการแก้ปัญหา การให้เหตุผล และการนำเสนอตัวแทนความคิด   คำสำคัญ : การคิดเชิงคณิตศาสตร์  การสอนแนะให้รู้คิด (CGI)  เทคนิคการใช้คำถามของบาดแฮม (Badham)   Abstract      The purpose of this research were 1) to compare mathematical thinking of mathayomsuksa 1 students before and after learning activities based on Cognitive Guided Instruction and questioning techniques of Badham and 2) to compare mathematical thinking of mathayomsuksa 1 students after learning activities based on Cognitive Guided Instruction and questioning techniques of Badham with the determined criterion of 70 percent of the test score. The sample was 27 mattayomsuksa 1 students in the second semester of 2014 academic year. The research instruments were lesson plans based on Cognitive Guided Instruction and questioning techniques of Badham, mathematical thinking tests, interview and observation. The data were analysed by Mean, standard deviation, t-test statistic and analytic induction. The research found that 1) student’s mathematical thinking after learning activities based on Cognitive Guided Instruction and questioning techniques of Badham of is higher than before at .05 level of statistical significance. Comparing mathematical thinking in problem solving, reasoning and representation are also higher than before at .05 level of statistical significance. 2) student’s mathematical thinking after learning activities based on Cognitive Guided Instruction and questioning techniques of Badham is higher than the determined criterion of 70 percent of the test score at .05 level of statistical significance. In conclusion, learning activities based on Cognitive Guided Instruction and questioning techniques of Badham facilitate students to solve the problem in various and different ways based on student’s competency. Students have more chance to talk and present their ideas to the classroom. In addition, questioning is able to motivate student’s thinking and reasoning when they answer the question that bring about the development of their mathematical thinking in problem solving, reasoning and representation.   Keywords : Mathematical Thinking, Cognitive Guided Instruction (CGI), Questioning Techniques on Badham
Keywords: การคิดเชิงคณิตศาสตร์ การสอนแนะให้รู้คิด (CGI) เทคนิคการใช้คำถามของบาดแฮม (Badham) Mathematical Thinking, Cognitive Guided Instruction (CGI), Questioning Techniques on Badham